Enhancing Quranic Literacy for Activists of Karang Taruna Using Digital Quran Memorization: Peningkatan Literasi Qur’an bagi Aktivis Karang Taruna Menggunakan Qur’an Digital Hafalan - Haryono*, Kholid; Safitri, Junaidi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This paper focuses on enhancing Qur'anic literacy in Indonesia through the development and implementation of the Tikrar digital Qur'an application. Although a survey by the Directorate General of Islamic Guidance of the Ministry of Religious Affairs shows high Qur'anic literacy with a score of 66.038, the number of Qur'an memorizers is still low compared to other countries. The Tikrar application was developed to facilitate the memorization process for the wider community. The study aimed to implement the application through community service activities at Karang Taruna, Yogyakarta, using the halaqah (group) method. Twenty-four participants were divided into four groups, engaging in activities that included reviewing and expanding the application's content and training sessions. Participants provided positive feedback, indicating that the application helped and motivated them to memorize the Qur'an. The halaqah method effectively enhanced motivation and memorization skills, demonstrating the application's potential to improve Qur'anic literacy in the community.